2018
DOI: 10.1007/s11837-018-3057-z
|View full text |Cite
|
Sign up to set email alerts
|

Phase Field Simulation of Dendritic Solidification of Ti-6Al-4V During Additive Manufacturing Process

Abstract: In this study, the phase field method is applied to simulate the phase transformation of Ti-6Al-4V from liquid phase to solid phase during solidification. The simulated results show the dendritic arms grow along the direction of the heat flow. Droplets are found formed inside dendrites. Solute enriches in the liquid near the dendritic tips and between dendritic arms. The effects of various processing parameters, including local temperature gradient, scan speed and cooling rate, on dendrites morphology and grow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(17 citation statements)
references
References 47 publications
1
16
0
Order By: Relevance
“…This agrees with the experimental observation by Yadroitsev et al [41]. Depending on the processing conditions, there are two possible grain structure types commonly found in welded metal [62,[64][65][66][67]. One type is the "competitive grain growth", where the grains at the fusion line may initially be oriented in a favorable direction for growth, but their direction may become unfavorable as the curved solid/liquid interface changes its position.…”
Section: Effect Of Scan Speed On Melt Pool and Microstructuressupporting
confidence: 88%
“…This agrees with the experimental observation by Yadroitsev et al [41]. Depending on the processing conditions, there are two possible grain structure types commonly found in welded metal [62,[64][65][66][67]. One type is the "competitive grain growth", where the grains at the fusion line may initially be oriented in a favorable direction for growth, but their direction may become unfavorable as the curved solid/liquid interface changes its position.…”
Section: Effect Of Scan Speed On Melt Pool and Microstructuressupporting
confidence: 88%
“…In a class of AM processes, each layer is built by repeated melting manufacturing have been used as input to simulate the solidification microstructures under directional solidification conditions. Wu and Zhang [7] performed simulations of the solidification microstructure of Ti-6Al-4V alloy assuming it to be a pseudo-binary of Ti with 10% solute for which a linear liquidus slope was specified along with a solidus and liquidus temperature. The 2D simulations showed the formation of a columnar structure after the breakdown of a planar morphology under the given values of G and R. The main disadvantage of the phase field model used was that it was not integrated with the thermodynamics of the ternary alloy.…”
Section: Introductionmentioning
confidence: 99%
“…The interface thickness is 5 units. Referring to the research of Gong et al [18][19][20], some physical parameters are obtained, as shown in Table 1. Table 1.…”
Section: Model Of Phase Fieldmentioning
confidence: 99%
“…Yang et al's research [13][14][15][16][17] concentrated on the finite element model for additive manufacturing, and the temperature field distribution of the additive manufacturing process was obtained, while macroscopic temperature field data were not introduced into the microstructure simulation, and there was a lack of description of the phase transition process. Gong et al [18][19][20] studied the microstructure evolution of EBAM Ti-6Al-4V during solidification, while the microstructure simulation of Ti-6Al-4V processed by SLM was unattended. Through the combination of macroscopic finite element simulation and microscopic phase field simulation, this paper attempts to bring the influence of macroscopic parameters into the microstructure.…”
Section: Introductionmentioning
confidence: 99%